Edukasi Dan Implementasi Biopori Serta Eco-Enzyme Dalam Mendukung Pemanfaatan Sampah Organik Di Nagari Kampung Batu Dalam - Indah Muliati; Winda Rahmawati; Alya Nabila; Iin Yunita; Maulani Azizah; Mutiara Sani; Naurah Fakhirah Hardiyanto (GLOBAL SCIENTS PUBLISHER, 2026)
Organic waste is the most common type of waste produced by the community, especially in rural areas with dominant agricultural activities. Suboptimal management of organic waste has the potential to cause environmental pollution and reduce public health. This Community Service Program (KKN) aims to improve the knowledge and skills of the Kampung Batu Dalam community in managing organic waste through education and the implementation of biopore technology and the use of Eco-Enzyme. The method used is a qualitative descriptive approach with participatory methods, including preparation, outreach, and training stages that directly involve the community. Data collection was carried out through observation, interviews, documentation, and field practice. The results of the activity showed that the community was enthusiastic about participating in the outreach and training on making Eco-Enzyme and Biopore Infiltration Holes (LRB). The implementation of this program was able to increase public awareness of the importance of organic waste management and provide an alternative waste treatment that is environmentally friendly and useful. Thus, this activity contributes to supporting sustainable organic waste management and improving environmental quality in Kampung Batu Dalam